Early English poetic culture and meter : the influence of G.R. Russom - Toswell, M. J.; Brady, Lindy (Festschriften, occasional papers, and lectures, 2016)
"This volume develops Geoffrey Richard Russom's contributions to early English metre and style, including his fundamental reworkings and rethinkings of accepted and oft-repeated mantras."--